Prevalence of Blastocystis sp. in cattle, goat and sheep reared by different farm management systems in Pahang, Malaysia - Nur Atiqah Abd Razak,; Mardhiah Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Blastocystis sp. is a familiar parasite in the gastrointestinal tract causing infection in humans and animals. The purpose of this study is to evaluate the Blastocystis sp. prevalence in three sorts of livestock; cattle, goats, and sheep in Pahang, Malaysia, which are reared under two management systems; intensive and semi-intensive farm management system. About 92, 96, and 65 cattle, goat, and sheep fecal samples respectively were collected from different farms around Kuantan, Bera, and Pekan. The fecal samples were cultured in Jones’ medium supplemented with 10% heat-inactivated horse serum and incubated at 37 ºC for 2 weeks, then observed under light microscopy daily. The total prevalence of Blastocystis sp. was 29.34% in cattle (27/92), 29.16% in goats (28/96), and 43.07% in sheep (28/65). Supported the results of this study, Blastocystis sp. prevalence was higher in sheep and livestock reared by a semi-intensive farm management system (44.38%). However, further study could be done for Blastocystis sp. subtypes identification to determine its genetic diversity. Notwithstanding, this study has provided additional knowledge on the prevalence of each livestock reared in farms around Pahang that serve as important information in understanding host-parasite relationships, besides determining the best farm management system to be applied by farmers.